Strain Hardening of Bainitic and Martensitic Steel in Compression; Steel in Translation; Vol. 48, iss. 10 - Aksenova K. V.; Nikitina E. N.; Ivanov Yu. F. Yuriy Fedorovich; Kosinov D. A. (2018, 2018)
Title screen